Street Participatory Action Research (Street PAR) With Hard-to-Reach Black Women and Girls: Advancing an Intersectional Criminological Approach - Hitchens, Brooklynn (Journal of contemporary criminal justice, 2025)
This article employs an intersectional criminological approach to examine how street participatory action research (Street PAR) engages marginalized Black women and girls involved in the streets and/or criminal legal system. Research on their offending and victimization presents unique methodological challenges, particularly in accessing racially stigmatized populations participating in illegal activities or facing economic and social precarity. Traditional “deficit” approaches often overlook the complex, racialized lived experiences of these women. Street PAR fosters collaboration by integrating street-identified Black men and women at all research stages, from design to intervention. Drawing from its implementation in Wilmington, Delaware, this article highlights key insights, including an analysis of study data on sexual violence, which reveals its profound impact on participants’ worldviews. By centering their voices and experiences, this study underscores the importance of Street PAR in capturing the depth of these findings and advocating for research methodologies that prioritize community engagement. Ultimately, this work demonstrates how Street PAR not only informs mixed-methods approaches, but also provides a more inclusive and ethical framework for studying other hard-to-reach populations on sensitive issues.